Evaluation of Flood Control Performance in the Talangsari Watershed, Samarinda, East Kalimantan - Hariyadi, Joko Sugeng; Istiarto, Istiarto; Raharjo, Adam Pamudji (Universitas Negeri Yogyakarta, 2023)
The flood issues in the Talangsari River in Samarinda City were not only caused by high rainfall but also by the significant sediment accumulation and waste along the river, the encroachment of residential areas onto the river section, and the lack of public awareness regarding environmental cleanliness. As a result, flooding occurs throughout the Talangsari River, from upstream to downstream, indicating significant damage to the river. Considering these issues, proactive measures are necessary to address the flood problems. One such measure is the normalization of the Talangsari River to ensure smooth land transportation from and to Apt Pranoto Airport in the Sei Siring area, Bontang City, Sangatta, and Kutai Kartanegara. The flood discharge plan was estimated using Nakayasu and SCS synthetic unit hydrograph method. The analysis revealed a peak discharge of 6.39 m3/s for the existing conditions (2-year return period) and 13.38 m3/s for the normalization conditions (25-year return period). Subsequently, the simulations were performed using the HEC-RAS program by two scenarios: the existing river condition and the normalization scenarios. Following the simulation with the 2-year return period discharge for the existing conditions, the Talangsari River experienced upstream to downstream flooding, underscoring the need for flood mitigation measures. The river normalization simulation using the 25-year return period discharge considered dimensions such as a channel width of 7m and a depth of 3.5m. As a result of the normalization simulation, the Talangsari River successfully accommodated a flow of 13.38 m3/s without experiencing flooding, confirming that the decision to pursue normalization was the best choice.